LABOUR MIGRATION INFLUENCE ON THE FUTURE FAMILY LIFE OF LABOUR MIGRANTS’ CHILDREN - KRUPNIK , IVAN (Journal of Vasyl Stefanyk Precarpathian National University, 2019)
In the article peculiarities of ideas about future family life of children from labor migrants' families are studied and analyzed in comparison with ideas of children from complete functional families and orphan children. It is noted that the reason for differences in family ideas is the influence of family deprivation. The author emphasizes the differences of ideas about the future family life of children from labor migrants' families (functionally incomplete families) in which parents work abroad for a long time from the ideas of orphan children. The children aged 13-14 took part in the research. The survey was conducted in different regions of Ukraine. It is assumed, that children deprived of parental guardianship will have the lowest level of formation of future family ideas. Consequently children of labor migrants, who suffer from parents’ absence less than orphan children, will take average positions between children from complete families and orphan children. The comparative characteristic of groups of teenagers was provided by the results of the research.